Is There a Capital Shortage: Theory and Recent Empirical Evidence - Andersen, Leonall C. (Journal of Finance, 1976)
Leonall C. Andersen, Is There a Capital Shortage: Theory and Recent Empirical Evidence, The Journal of Finance, Vol. 31, No. 2, Papers and Proceedings of the Thirty-Fourth Annual Meeting of the American Finance Association Dallas, Texas December 28-30, 1975 (May, 1976), pp. 257-268